Structural design and analysis of exoskeleton handling robot based on virtual simulation technology in artificial intelligence environment - Menon, Dr.Satish (The journal of contemporary issues in business and government, 2022)
With the rapid development of our economy and the acceleration of the aging of the population, more and more manual jobs can not find suitable candidates, and the exoskeleton assisted transport robot(EATR) has become a research hotspot. Most of the existing exoskeleton assisted robots at home and abroad are expensive and complex in structure, which is not suitable for the actual needs of ordinary workers in India. Based on the virtual simulation technology(VST), the structure of exoskeleton assisted handling robot(EAHR) is designed and studied in this paper. Through the VST, the virtual prototype of the bone assisted handling robot is simulated, and the virtual prototype model of the exoskeleton robot(ER) is established. The driving function of each joint handling action is established for the human body(HB) handling action. The simulation results show that the movement trajectory of the lower limb joints of the ER is almost identical with the input angle of the lower limb joints of the HB's gait movement, and has high response and stability characteristics.